Muffins Elaborated with Optimized Monoglycerides Oleogels: From Solid Fat Replacer Obtention to Product Quality Evaluation - Giacomozzi, Anabella Soledad (2018)
This study demonstrates the effectiveness of using oleogels from high oleic sunflower oil (HOSO) and monoglycerides as solid fat replacers in a sweet bakery product. Firstly, a methodology to obtain oleogels with desired properties based on mathematical models able to describe relationships between process and product characteristics variables followed by multi-objective optimization was applied. Later, muffins were prepared with the optimized oleogels and their physicochemical and textural properties were compared with those of muffins formulated using a commercial margarine (Control) or only HOSO. Furthermore, the amount of oil released from muffins over time (1, 7, and 10 days) was measured to evaluate their stability. The replacement of commercial margarine with the optimized oleogels in muffin formulation led to the obtention of products with greater spreadability, higher specific volume, similar hardness values, and a more connected and homogeneous crumb structure. Moreover, these products showed a reduction of oil migration of around 50% in contrast to the Control muffins after 10 days of storage, which indicated that the optimized oleogels can be used satisfactorily to decrease oil loss in this sweet baked product. Fat replacement with the optimized monoglycerides oleogels not only had a positive impact on the quality of the muffins, but also allowed to improve their nutritional profile (without trans fat and low in saturated fat).